Gambaran Kebahagiaan dan Karakteristik Positif Perempuan Dewasa Madya yang Menjadi Caregiver Informal Penderita Skizofrenia - Rima Nadya Widyanti; Dini Rahma Bintari (Fakultas Psikologi Universitas Pancasila, 2010)
Schizophrenia is a severe mental disorder which commonly occurs in people who live in big cities such as Jakarta. People with schizophrenia may cause problems to their family, particularly to their caregivers, and the problems may affect caregivers' happiness. Seligman (2005) divides happiness into three periods of life; past, present, and future. The application of positive character in daily life, particularly in their role as caregivers, also influences their happiness. This study was conducted to examine happiness and positive character of middle-aged women who became informal caregivers for people with schizophrenia. Qualitative method through interview and observation was used to analyze the data. Respondents were four women, aged 40-65. The result showed diversity of happiness in the subjects, depending on their positive emotion in the past, present, and future life. Their happiness was also influenced by care-receivers' conditions and their dependability on the caregivers. Positive character also kept the subjects strong to take varios responsibility and other roles.